2000
DOI: 10.1053/euje.2000.0043
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Right Ventricle in Left Ventricular Hypertrophic Cardiomyopathy: Analysis by Pulsed Doppler Tissue Imaging

Abstract: This study shows the usefulness of pulsed Doppler tissue imaging to detect impairment of right ventricular myocardial function and to provide evidence about ventricular interaction in forms of hypertrophic cardiomyopathy which involve interventricular septum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 15 publications
5
44
1
5
Order By: Relevance
“…These studies also demonstrated that RV and interventricular septum hypertrophy seem to be the major factors influencing the RV functions in systemic hypertension [33, 34]. Similarly elevated LV filling pressure can translate to elevated RV pressure and hence RV abnormalities.…”
Section: Discussionmentioning
confidence: 97%
“…These studies also demonstrated that RV and interventricular septum hypertrophy seem to be the major factors influencing the RV functions in systemic hypertension [33, 34]. Similarly elevated LV filling pressure can translate to elevated RV pressure and hence RV abnormalities.…”
Section: Discussionmentioning
confidence: 97%
“…These velocities have also been related with a stage of cardiac failure in heart transplant patients [17]. The right ventricular relaxation time and the early/late diastolic velocity ratio have been related to the involvement of the right ventricle in left ventricular hypertrophic cardiomyopathy and hypertension [18, 19]. …”
Section: Discussionmentioning
confidence: 99%
“…Pressões diastólicas aumentadas são necessárias devido à rigidez e à menor distensibilidade ventricular (Severino et al 2000, Chetboul et al 2006b, Gundler Tidholm & Haggstrõm 2008. O ventrículo esquerdo, mais rígido, requer pressões de enchimento maiores e, consequentemente, as pressões diastólicas atriais e ventriculares aumentam (Kato et al 2007, Ware 2007, Koffas et al 2008.…”
Section: Introductionunclassified